'Pet ke waaste': Rights, resistance and the East Indian Railway Strike, 1922. (January 2014) - Webb, Silas
At its peak, the East Indian Railway strike of 1922 affected more than 1500 kilometres of rail and involved tens of thousands of workers. The strike was an exemplary moment in Indian worker politics. It advanced an idiom of citizenship, distinct from Gandhian non-cooperation and Congress nationalism, in order to make claims for redress on their employer and the state, and simultaneously, to exhibit profound social power against the colonial state and would-be nationalist representatives. Though this strike began in response to allegations of a brutal assault, the demands of the workers, I will argue, expose the limits of both political nationalism and colonialism. To establish this point, the EIR strike is placed in a trans-colonial context with Kenya, which allows for the appreciation of the interwar period as a transformative moment in worker politics. Not only did the Indian strike actively resist Gandhi's proscriptions on striking and maintaining financial ties to the railway company, the workers also moved against the authority of the colonial state by appropriating discourses of governance that were conventionally used against them. Thus, while the strike relied on the breakdown of colonial authority resulting from nationalist agitation, the strike exceeded the purview of elite politics.